2015
DOI: 10.1556/168.2015.16.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Litter quality and temperature modulate microbial diversity effects on decomposition in model experiments

Abstract: Abstract:The consequences of decline in biodiversity for ecosystem functioning is a major concern in soil ecology. Recent research efforts have been mostly focused on terrestrial plants, while, despite their importance in ecosystems, little is known about soil microbial communities. This work aims at investigating the effects of fungal and bacterial species richness on the dynamics of leaf litter decomposition. Synthetic microbial communities with species richness ranging from 1 to 64 were assembled in laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In our study, we could not show a direct effect of soil microbial diversity on soil ecosystem functions such as litter decomposition. Since decomposition is a complex process, which involves interaction of different bacterial and fungal functional guilds 44 , it is assumed to be higher in soils with higher microbial richness 45 . However, evidence from field studies is largely lacking.…”
Section: Soil Functionsmentioning
confidence: 99%
“…In our study, we could not show a direct effect of soil microbial diversity on soil ecosystem functions such as litter decomposition. Since decomposition is a complex process, which involves interaction of different bacterial and fungal functional guilds 44 , it is assumed to be higher in soils with higher microbial richness 45 . However, evidence from field studies is largely lacking.…”
Section: Soil Functionsmentioning
confidence: 99%
“…Understanding the direction and extent of microbial interactions is of key importance for predicting the patterns of ecosystem processes under varying environmental pressures. Experiments on litter decomposition dynamics have shown that positive interactions may enhance leaf litter degradation (Bani et al, 2019) while competitive interactions among multi‐species microbial consortia were reported to negatively affect litter and wood decomposition (Boddy, 2000; Bonanomi et al, 2015; Cox et al, 2001). However, positive co‐occurrences may just reflect similar habitat requirements of the species involved with no effect on process rates and/or a lack of competitive exclusion (Odriozola et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic initial biochemical characteristics of plant litter are major factors driving its decomposition rate [ 26 , 53 , 54 ], hence directly or indirectly affecting interconnecting ecological processes, including litter nutrient dynamics [ 55 57 ] and suitability for microbial feeding [ 58 60 ], phytotoxicity [ 29 , 61 ] and plant-soil negative feedback [ 27 ]. Surprisingly, few studies attempted to relate the biochemical characteristics of different organic products with their effect on SWR.…”
Section: Discussionmentioning
confidence: 99%